Coating containing pigment with heat insulation function and preparation method of coating
By coating the thermal insulation functional pigment and silica coating, combined with organic ligand and polyvinyl alcohol for catalytic reaction, coating with integrated coloring and heat insulation functions was prepared, which solved the problem of reduced adhesion and hardness of existing coatings during use, and achieved efficient thermal insulation effect and good coating performance.
Patent Information
- Application Number
- CN202411979185.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing thermal insulation coatings are likely to reduce the adhesion and hardness of the coating during use, and the thermal insulation effect is greatly affected by the packing properties and use environment factors.
By coating the thermal insulation functional pigment and coating the silica sol-gel method, and catalytic reactions are carried out by combining organic ligands and polyvinyl alcohol to prepare a coating with integrated coloring and thermal insulation functions.
The leveling of the paint and the formation of a uniform coating film is achieved, while the thermal insulation effect is enhanced, the filler covers the pigment color, and the adhesion and hardness of the coating are improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a coating containing a heat-insulating functional pigment and a preparation method thereof. Background Art
[0002] In the coating components, functional pigments are collectively referred to as pigments with specific functions such as anti-fouling, temperature indication, luminescence, and rust prevention, which are different from ordinary pigments that are mainly used for coloring. They play an important role in coatings. Thermal insulation functional pigments are materials that can reflect or absorb solar radiation heat, thereby reducing the surface temperature of objects. Common thermal insulation functional pigments mainly include reflective and barrier types. Reflective pigments mainly include infrared reflective pigments, and barrier pigments mainly include a mixture of thermal insulation fillers such as SiO2 aerogel, hollow glass microspheres, and hollow ceramic microspheres and pigments. For example, CN116851235B discloses a reflective thermal insulation colorful coating.
[0003] In actual use and research, it was found that although SiO2 aerogel can provide excellent thermal insulation for coatings, it affects the adhesion and hardness of the coatings. The coatings are prone to cracking and powdering in the later stage and need to be repainted to maintain their thermal insulation effect. Excessive addition of hollow glass microspheres and hollow ceramic microspheres as barrier fillers will result in the coating failing to fully wrap the above fillers, thus weakening the film-forming effect, the glossiness of the coating surface, and the light reflection ability, thereby weakening the thermal insulation effect. After high-temperature treatment, the interaction force between the molecules of the infrared reflective pigment is strong, and it is easy to agglomerate and difficult to disperse. The compatibility with the coating matrix is poor. At present, a layer of film is successfully formed on the surface of the pigment particles to form a core-shell structure to improve the dispersibility of the material. For example, CN103725074B discloses a high-temperature resistant thermal insulation coating, but the pigment with a core-shell structure will cause damage to the pigment itself during the process of core-shell formation. There are also studies reporting that the pigment with a core-shell structure may degrade in function due to humidity, temperature, light and other factors, and the thermal insulation performance of the infrared reflective pigment after being added to the coating depends on the cleanliness of the coating surface, which limits the scope of use of the coating. Summary of the invention
[0004] The object of the present invention is to provide a coating containing a heat-insulating functional pigment and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions: The present invention provides a coating containing a heat-insulating functional pigment. The raw materials for preparing the coating include the following raw material components by weight: 40-60 parts of an aqueous resin dispersion, 15-20 parts of a heat-insulating functional pigment, 0.1-0.2 parts of a defoamer, 0.01-0.5 parts of a dispersant, 0.1-0.5 parts of a leveling agent, and 0.5-1 parts of a film-forming aid; The heat-insulating functional pigment is obtained by coating the pigment and then coating it with silica sol-gel method and then reacting it with organic ligand for catalysis.
[0006] Furthermore, the solid content of the aqueous resin dispersion is 30-50wt%; the aqueous resin dispersion is one or a combination of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane, aqueous acrylic-silicone resin.
[0007] Furthermore, the preparation method of the heat-insulating functional pigment comprises the following steps: (1) The dried pigment is uniformly dispersed in ethanol, polyacrylamide is then added dropwise to the ethanol, and the mixture is stirred and mixed under heating, and the coated pigment is obtained after solid-liquid separation; (2) mixing tetraethoxysilane with an ethanol solution, adjusting the pH to a strong acid, reacting under heating, adjusting the pH to a weak base after the reaction is completed, rapidly stirring and then standing, uniformly dispersing the coated pigment in the standing solution, heating and stirring, centrifuging and washing, and vacuum drying to obtain a silica-coated pigment; (3) The silica-coated pigment, organic ligand and polyvinyl alcohol are mixed and dissolved in an organic solvent, a catalyst is added to heat the mixture for reaction, and the reaction product is washed and dried to obtain the heat-insulating functional pigment.
[0008] Furthermore, in step (1): The mass concentration of the ethanol is 95wt%; The mass ratio of the polyacrylamide to the pigment is 1:10; The stirring and mixing under the heating state specifically comprises stirring at a temperature of 60-70° C. for 0.5-1 h.
[0009] Furthermore, in step (2), the mass concentration of the ethanol solution is 75wt%.
[0010] Furthermore, step (2) specifically includes the following steps: Mix tetraethoxysilane and ethanol solution in a mass ratio of 1: (10-12), add concentrated hydrochloric acid to adjust the pH to 2-3, react at 50-60°C for 5-6 hours, and after the reaction, add sodium hydroxide solution to adjust the pH to 7-8, stir rapidly and let stand for 30-40 minutes; The coated pigment is uniformly dispersed in the static solution at a mass ratio of 1:4, heated to 50-60° C., stirred for 1-2 hours, and then centrifuged for washing. The silica-coated pigment is obtained after vacuum drying at 20-25° C. for 24 hours to 48 hours.
[0011] Furthermore, step (3) specifically includes the following steps: The silica-coated pigment, organic ligand and polyvinyl alcohol are mixed and dissolved in a sufficient amount of organic solvent in a mass ratio of 100: (4-6.4): (0.8-2.4), and catalyst acetic acid is added to heat and react at 120° C. for 12-24 hours. The reaction product is washed three times with tetrahydrofuran, acetone and ethanol, and then placed in a vacuum drying oven at 60° C. for drying for 24 hours to obtain the heat-insulating functional pigment.
[0012] Furthermore, the organic ligand is one of trimesaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarbaldehyde, terephthalaldehyde, 2,5-dihydroxyterephthalic acid, 2,3,5,6-tetrafluoroterephthalic acid, and terephthalic acid.
[0013] Furthermore, in step (3), the organic solvent is one of tetrahydrofuran, acetone and ethanol.
[0014] The present invention also provides a method for preparing the above-mentioned coating containing heat-insulating functional pigments, comprising: putting the aqueous resin dispersion into a dispersion kettle and dispersing it at a speed of 1000-1200rpm for 5-20min, then putting the heat-insulating functional pigment into the dispersion kettle and mixing it evenly with the aqueous resin dispersion to obtain a mixed slurry, then adding a defoamer, a dispersant, and a leveling agent into the mixed slurry, and ball-milling the mixed slurry at a speed of 500-1000rpm for 1-5h to obtain a coating.
[0015] The beneficial effects of the present invention are: The heat-insulating functional pigment proposed in the present invention integrates coloring and heat insulation. Compared with the use of heat-insulating fillers and pigments separately, it avoids affecting the leveling of the coating and forming a coating film with uniform texture, and at the same time can reduce the covering of the filler on the pigment color.
[0016] During the treatment process, the pigment particles of the present invention are in a protected state, which can fully retain the color of the pigment particles and meet the use of coatings of different systems; the heat insulation effect is significant compared with heat insulation fillers such as SiO2 aerogel, hollow glass microspheres and hollow ceramic microspheres, and at the same time has good adhesion and excellent hardness.
[0017] The heat-insulating functional pigment proposed by the present invention has good dispersibility and is not easy to agglomerate in the coating. The interaction force between the heat-insulating functional pigment and the coating matrix is strong. Compared with SiO2 aerogel, it is not easy to powder and crack. Compared with hollow glass microspheres and hollow ceramic microspheres, it has stronger encapsulation with the aqueous resin dispersion. DETAILED DESCRIPTION
[0018] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0019] 1. Materials Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0020] The method for preparing the heat-insulating functional pigment in the raw material for preparing the coating of the present invention comprises the following steps: (1) The dried pigment is uniformly dispersed in ethanol with a mass concentration of 95wt%, and then a polyacrylamide solution (v / v=1:1 with water) with a mass of 1 / 10 of the pigment is added dropwise to the ethanol, and the mixture is heated and stirred at 60-70°C for 0.5-1h, and then the solid-liquid separation is performed to obtain a solid coated pigment, which is then dried at 40°C for later use; (2) Tetraethoxysilane and ethanol solution are mixed in a mass ratio of 1: (10-12), concentrated hydrochloric acid is added dropwise to adjust the pH to 2-3, and the mixture is reacted at 50-60°C for 5-6 hours. After the reaction is completed, sodium hydroxide solution is added dropwise to adjust the pH to 7-8, and the mixture is rapidly stirred and allowed to stand for 30-40 minutes; the coated pigment is uniformly dispersed in the solution in a mass ratio of 1:4 after standing, and the mixture is heated to 50-60°C, stirred for 1-2 hours, and then centrifuged for washing. The silica-coated pigment is then dried at 20-25°C in a vacuum for 24 hours to 48 hours to obtain the silica-coated pigment; (3) The silica-coated pigment, organic ligand and polyvinyl alcohol are mixed and dissolved in a sufficient amount of organic solvent in a mass ratio of 100:(4-6.4):(0.8-2.4), and acetic acid is added as a catalyst to heat the reaction at 120°C for 12-24 hours. The reaction product is washed three times with tetrahydrofuran, acetone and ethanol, and then placed in a vacuum drying oven at 60°C for drying for 24 hours to obtain a heat-insulating functional pigment.
[0021] 2. Methods 2.1 Preparation In this experiment, titanium nickel yellow 1053A was selected as the research pigment. The water-based resin dispersion liquid selected a commercial water-based acrylic resin with a solid content of 30-50wt%, the dispersant selected a commercial BYK-164 dispersant, the defoamer selected a commercial EFKA-2526 defoamer, the leveling agent selected a commercial BYK-358N leveling agent, and the film-forming aid selected a commercial Texanol film-forming agent.
[0022] 2.1.1 Preparation of coated titanium nickel yellow The dried titanium nickel yellow was evenly dispersed in ethanol with a mass concentration of 95wt% to obtain a color slurry, and then a solution of polyacrylamide with a mass of 1 / 10 of the titanium nickel yellow (v / v=1:1 with water) was added dropwise to the ethanol, and then the mixture was heated and stirred at 62°C for 1h, and then the solid-liquid separation was performed by suction filtration to obtain a solid coated titanium nickel yellow, which was then dried at 40°C for later use.
[0023] 2.1.2 Preparation of silica-coated titanium nickel yellow by sol-gel method Tetraethoxysilane and 75wt% ethanol were mixed in a mass ratio of 1:10, concentrated hydrochloric acid was added dropwise to adjust the pH to 3, and the mixture was reacted at 50-60°C for 5 hours. After the reaction, sodium hydroxide solution was added dropwise to adjust the pH to 8, and the mixture was allowed to stand for 40 minutes after rapid stirring. Coated titanium nickel yellow was evenly dispersed in the solution in a mass ratio of 1:4 after standing, and the mixture was heated to 60°C and stirred for 2 hours, then centrifuged and washed, and dried in vacuo at 25°C for 48 hours to obtain silica-coated titanium nickel yellow.
[0024] 2.1.3 Preparation of heat-insulating pigments Silica-coated titanium nickel yellow, trimesaldehyde and polyvinyl alcohol are put into a reactor at a mass ratio of 100:6.4:2.0 and mixed, and a sufficient amount of ethanol is added, and then 5% of the total system mass of catalyst acetic acid is added. The reactor temperature is raised to 120°C and heated to react for 24 hours. The reaction product is washed three times with tetrahydrofuran, acetone and ethanol, and then placed in a vacuum drying oven at 60°C for drying for 24 hours to obtain a heat-insulating functional pigment.
[0025] 2.1.4 Coating preparation By weight, 60 parts of aqueous acrylic resin dispersion were put into a dispersion kettle and dispersed at a speed of 1000 rpm for 10 minutes, and then 20 parts of heat-insulating functional pigments were put into the dispersion kettle and mixed evenly with the aqueous acrylic resin dispersion to obtain a mixed slurry, and then 0.1 parts of defoaming agent, 0.02 parts of dispersant, 0.2 parts of leveling agent, and 0.5 parts of film-forming aid were added to the mixed slurry, and the mixed slurry was ball-milled at a speed of 500 rpm for 2.5 hours to obtain a coating.
[0026] 2.2 Coating performance test and conclusion 2.2.1 Experimental group preparation The coating prepared in 2.1.4 is taken as Group 1, and 80 parts of aqueous acrylic resin dispersion, 0.1 parts of defoamer, 0.02 parts of dispersant, 0.5 parts of leveling agent, and 0.5 parts of film-forming aid are ball-milled at 500 rpm for 2.5 h to obtain a coating as Group 2; 10 parts of titanium nickel yellow, 10 parts of SiO2 aerogel and 60 parts of dispersed aqueous acrylic resin dispersion were put into a dispersion kettle and mixed evenly to obtain a mixed slurry. Then 0.1 parts of defoaming agent, 0.02 parts of dispersant, 1 part of leveling agent and 0.8 parts of film-forming aid were added to the mixed slurry. The mixed slurry was ball-milled at 500 rpm for 2.5 hours to obtain a coating, which was referred to as Group 3.
[0027] 10 parts of titanium nickel yellow, 5 parts of hollow glass microspheres, 5 parts of hollow ceramic microspheres and 60 parts of dispersed aqueous acrylic resin dispersion were put into a dispersion kettle and mixed evenly to obtain a mixed slurry. Then 0.1 parts of defoaming agent, 0.02 parts of dispersant, 2 parts of leveling agent and 1 part of film-forming aid were added to the mixed slurry. The mixed slurry was ball-milled at 500 rpm for 2.5 hours to obtain a coating, which was referred to as Group 4.
[0028] 2.2.2 Testing Thermal conductivity: Stir the four groups of coatings evenly and spray them on the substrate with release paper attached. After spraying, cure the substrate until a uniform and stable coating is formed on the substrate with a thickness of not less than 0.8mm. Tear off the release paper to obtain the test sample. Get 5 samples for each group of coatings. Use the heat flow meter method to test the thermal conductivity of the above samples to obtain the thermal conductivity λ1. Soak the above samples in turn and perform high-temperature light aging for 50 cycles. Then test the thermal conductivity to obtain the thermal conductivity λ2. The change rate is (λ2-λ1) / λ1×100%, which is used as the basis for the weather resistance of the coating (thermal conductivity is an inherent property of the material, which mainly depends on the composition and structure of the material. When the internal structure of the material changes, the thermal conductivity will change). Among them, soaking: in deionized water at 20±2℃, 1000W ultrasound for 30min; high-temperature light aging: immediately pick up after soaking and place in an environment of 240℃ and 0.02kW×3 UV aging lamps for 30min.
[0029] Insulation temperature difference: According to the standard JC / T1040-2020 "Heat-reflective insulation coatings for building exterior surfaces".
[0030] Adhesion: According to standard GB / T 9286 "Scratch test for paint and varnish films".
[0031] Hardness: According to the standard GB / T 6739 "Paint and varnish pencil method for determination of paint film hardness".
[0032] Color difference and appearance: The above four groups of coatings were applied to the aluminum substrate and baked at about 60-80℃ for about 20-40min to form a film with a thickness of not less than 0.8mm. The sample film was aged in a xenon lamp aging test chamber with the following parameters: xenon lamp 2400h (3168KJ / m 2), based on the L*a*b system specified in the JIS Z 8729-2004 color specification, the absolute difference between the color of the sample film after irradiation and the initial color is used as the result of the color difference test, and the appearance of the sample film is observed to see if it is powdered, cracked or peeled.
[0033] The results of the above performance tests are shown in Table 1: Table 1 Test results of coating properties of groups 1-4 From the above test results, it can be seen that the coatings with added SiO2 aerogel, hollow glass microspheres and hollow ceramic microspheres have better thermal insulation effect than the blank group 2, and have a certain improvement in hardness, but the addition of fillers has a slight effect on adhesion. After high humidity and high temperature aging treatment of the coatings of groups 3-4, it can be seen that their thermal insulation effect cannot be effectively maintained, especially the coatings with added SiO2 aerogel, which expand after high humidity and high temperature light aging, resulting in dense pits on the surface of the coating, and its thermal conductivity cannot be measured. Although the coatings with added hollow glass microspheres and hollow ceramic microspheres can also maintain a good thermal insulation effect, the researchers speculate that it is due to the thermal insulation of the filler itself, and its poor encapsulation with the aqueous acrylic resin dispersion, resulting in a significant change rate of its thermal insulation effect, and both have defects in adhesion, hardness, color difference and appearance.
[0034] From the results of thermal conductivity and temperature difference, it can be seen that the thermal insulation effect of Group 1 coating is more significant than that of thermal insulation fillers such as SiO2 aerogel, hollow glass microspheres and hollow ceramic microspheres alone, and Group 1 coating also has good adhesion and excellent hardness.
[0035] The heat-insulating functional pigment of the present invention integrates coloring and heat insulation. Compared with the use of heat-insulating fillers and pigments separately, it avoids affecting the leveling of the coating and forming a coating film with uniform texture, and at the same time can reduce the covering of the filler on the pigment color.
[0036] 2.3 Study the influence of different aqueous dispersions on coating performance Based on 2.1, the effects of waterborne epoxy resin, waterborne polyurethane and waterborne acrylic-silicone resin on coating performance were studied.
[0037] The waterborne epoxy resin, waterborne polyurethane, and waterborne acrylic-silicone resin used in this test are all commercially available, with a solid content of 30-50wt%.
[0038] According to the preparation process of 2.1.4, the aqueous acrylic resin dispersion was replaced with 60 parts of aqueous epoxy resin dispersion (Group 5), aqueous polyurethane dispersion (Group 6), and aqueous acrylic-silicone resin dispersion (Group 7) to obtain coatings.
[0039] The above coatings were tested using method 2.2.2. The results of the performance test are shown in Table 2: Table 2 Test results of coating performance of groups 5-7 It can be seen from the above test results that the thermal conductivity of Group 6 coating is lower and the thermal insulation effect is better. This is because the thermal conductivity of waterborne polyurethane itself is lower than that of other dispersions. The thermal insulation functional pigment of the present invention can be applied to waterborne resin dispersions of different systems, all of which have good thermal insulation effects, small color difference, good weather resistance, and a certain level of adhesion and hardness.
[0040] 2.4 Study on the influence of the preparation method of heat-insulating functional pigments on coatings 2.4.1 Impact of the packaging and assembly process According to the preparation process of 2.1.4, the heat-insulating functional pigments are replaced according to the following raw materials: Titanium nickel yellow is used to replace the heat-insulating functional pigment to prepare a coating, which is group 8; The coated titanium nickel yellow prepared in 2.1.1 is used to replace the heat-insulating functional pigment to prepare a coating, which is group 9; The heat-insulating functional pigment is replaced with the silica-coated titanium nickel yellow prepared in 2.1.2 to prepare a coating, which is group 10; In the preparation process of 2.1.2, the uncoated titanium nickel yellow is coated by the sol-gel method, and the obtained coated pigment is used to replace the heat-insulating functional pigment to prepare a coating, which is group 11; The above coatings were tested using method 2.2.2. The results of the performance test are shown in Table 3: Table 3 Test results of coating performance of groups 8-11 It can be seen from the above test results that the present invention first uses polyacrylamide to protect the pigment, so that the pigment particles are in a protected state during the treatment process, and the vividness of the pigment particles can be fully retained. Then tetraethoxysilane is selected as the silicon source, and the silica-coated pigment is prepared by the sol-gel method, which can improve the density of the coating or paint film, increase the adhesion and hardness of the coating, inhibit the foaming and permeability of the coating, and also increase the heat insulation function of the pigment; and the silica gel coating layer can hinder the direct contact between the pigment and the surrounding medium and the external environment, and can also slow down its oxidative degradation of the surrounding organic matter. Finally, organic ligands and polyvinyl alcohol are used to form a composite material similar to an organic skeleton-silicon dioxide coated pigment with the silica-coated pigment. On the one hand, the refractive index can be increased to improve the heat insulation effect, and chemical bonds or physical crosslinking may be formed between the organic skeleton and the silica gel, and the silica gel can also play a supporting role, thereby enhancing the mechanical properties of the coating.
[0041] 2.4.2 Effects of inorganic and organic pigments In this experiment, titanium chrome brown HM-2401, cobalt blue HM-2801, and cobalt green HM-5002 were selected as inorganic pigments, and benzidine yellow COLORSTEP®O Yellow X1081 and carbazole violet COLORSTEP®O VIOLET B4023 were selected as organic pigments.
[0042] According to the preparation process of 2.1.1-2.1.3, the above-mentioned inorganic pigments and organic pigments are used to replace titanium nickel yellow. The difference is that the organic pigment does not need to be dispersed in 95wt% ethanol. A polyacrylamide solution with a mass concentration of 1 / 10 of the pigment is prepared (v / v with water = 1:1) and added dropwise to the slurry of the organic pigment. After three centrifugal washing processes, the organic pigment particles are obtained and replaced with the coated titanium nickel yellow in the process of 2.1.2.
[0043] According to the above process, six groups of heat-insulating functional pigments were obtained respectively, and then according to the preparation process of 2.1.4, the heat-insulating functional pigments were replaced to obtain coating group 12 (titanium chrome brown HM-2401), group 13 (cobalt blue HM-2801), group 14 (cobalt green HM-5002), group 15 (benzidine yellow), and group 16 (carbazole violet).
[0044] The above coatings were tested using method 2.2.2. The results of the performance test are shown in Table 4: Table 4 Test results of coating properties of groups 12-16 It can be seen from the above test results that the preparation method of the present invention is highly applicable to inorganic pigments, and the performance of inorganic pigments of different colors after treatment is not much different. However, the color difference of organic pigments decreases greatly. It is speculated that the reason is that the flocculation process of polyacrylamide and organic pigments is not a coating process, so that the organic pigments are affected by the solvent in the subsequent process, resulting in poor color difference stability and poor hardness.
[0045] 2.4.3 Effect of organic ligands In this experiment, 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, terephthalaldehyde, 2,5-dihydroxyterephthalic acid, 2,3,5,6-tetrafluoroterephthalic acid and terephthalic acid were selected as organic ligands.
[0046] According to the preparation process of 2.1.3, the above organic ligand is used to replace the trimesaldehyde in 2.1.3 to obtain a heat-insulating functional pigment.
[0047] According to the above process, five groups of heat-insulating functional pigments were obtained respectively, and then according to the preparation process of 2.1.4, the heat-insulating functional pigments were replaced to obtain coating group 17 (2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde), group 18 (terephthalaldehyde), group 19 (2,5-dihydroxyterephthalic acid), group 20 (2,3,5,6-tetrafluoroterephthalic acid), and group 21 (terephthalic acid).
[0048] The above coatings were tested using method 2.2.2. The results of the performance test are shown in Table 5: Table 5 Test results of coating properties of groups 17-21 From the above test results, it can be seen that the weather resistance of the coatings using 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde, terephthalaldehyde and trimesicarboxaldehyde as organic ligands is slightly better than that of 2,5-dihydroxyterephthalic acid, 2,3,5,6-tetrafluoroterephthalic acid and terephthalic acid, and the effect is significant in the change of weather resistance.
[0049] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A coating containing a heat-insulating pigment, characterized in that: The raw materials for preparing the coating include the following raw material components by weight: 40-60 parts of aqueous resin dispersion, 15-20 parts of heat-insulating functional pigment, 0.1-0.2 parts of defoamer, 0.01-0.5 parts of dispersant, 0.1-0.5 parts of leveling agent, and 0.5-1 parts of film-forming aid; The heat-insulating functional pigment is obtained by coating the pigment and then coating it with silica sol-gel method and then reacting it with organic ligand for catalysis.
2. The coating containing heat-insulating pigment according to claim 1, characterized in that: The solid content of the aqueous resin dispersion is 30-50wt%; the aqueous resin dispersion is one or a combination of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane, aqueous acrylic-silicone resin.
3. The coating containing heat-insulating pigment according to claim 1, characterized in that: The preparation method of the heat-insulating functional pigment comprises the following steps: (1) The dried pigment is uniformly dispersed in ethanol, polyacrylamide is then added dropwise to the ethanol, and the mixture is stirred and mixed under heating, and the coated pigment is obtained after solid-liquid separation; (2) mixing tetraethoxysilane with an ethanol solution, adjusting the pH to a strong acid, reacting under heating, adjusting the pH to a weak base after the reaction is completed, rapidly stirring and then standing, uniformly dispersing the coated pigment in the standing solution, heating and stirring, centrifuging and washing, and vacuum drying to obtain a silica-coated pigment; (3) The silica-coated pigment, organic ligand and polyvinyl alcohol are mixed and dissolved in an organic solvent, a catalyst is added to heat the mixture for reaction, and the reaction product is washed and dried to obtain the heat-insulating functional pigment.
4. The coating containing heat-insulating pigment according to claim 3, characterized in that: In step (1): The mass concentration of the ethanol is 95wt%; The mass ratio of the polyacrylamide to the pigment is 1:10; The stirring and mixing under the heating state specifically comprises stirring at a temperature of 60-70° C. for 0.5-1 h.
5. The coating containing heat-insulating pigment according to claim 3, characterized in that: In step (2), the mass concentration of the ethanol solution is 75wt%.
6. The coating containing heat-insulating pigment according to claim 5, characterized in that: Step (2) specifically includes the following steps: Mix tetraethoxysilane and ethanol solution in a mass ratio of 1: (10-12), add concentrated hydrochloric acid to adjust the pH to 2-3, react at 50-60°C for 5-6 hours, and after the reaction, add sodium hydroxide solution to adjust the pH to 7-8, stir rapidly and let stand for 30-40 minutes; The coated pigment is uniformly dispersed in the static solution at a mass ratio of 1:4, heated to 50-60° C., stirred for 1-2 hours, and then centrifuged for washing. The silica-coated pigment is obtained after vacuum drying at 20-25° C. for 24 hours to 48 hours.
7. The coating containing heat-insulating pigment according to claim 3, characterized in that: Step (3) specifically includes the following steps: The silica-coated pigment, organic ligand and polyvinyl alcohol are mixed and dissolved in a sufficient amount of organic solvent in a mass ratio of 100: (4-6.4): (0.8-2.4), and catalyst acetic acid is added to heat and react at 120° C. for 12-24 hours. The reaction product is washed three times with tetrahydrofuran, acetone and ethanol, and then placed in a vacuum drying oven at 60° C. for drying for 24 hours to obtain the heat-insulating functional pigment.
8. The coating containing heat-insulating pigment according to claim 7, characterized in that: The organic ligand is one of trimesaldehyde, 2,4,6-trihydroxy-1,3,5-benzenetricarbaldehyde, terephthalaldehyde, 2,5-dihydroxyterephthalic acid, 2,3,5,6-tetrafluoroterephthalic acid and terephthalic acid.
9. The coating containing heat-insulating pigment according to claim 7, characterized in that: In step (3), the organic solvent is one of tetrahydrofuran, acetone and ethanol.
10. A method for preparing a coating containing a heat-insulating pigment according to any one of claims 1 to 9, characterized in that: The aqueous resin dispersion is put into a dispersion kettle and dispersed at a speed of 1000-1200rpm for 5-20min, and then the heat insulation functional pigment is put into the dispersion kettle and mixed evenly with the aqueous resin dispersion to obtain a mixed slurry, and then a defoamer, a dispersant, and a leveling agent are added to the mixed slurry, and the mixed slurry is ball-milled at a speed of 500-1000rpm for 1-5h to obtain a coating.
Citation Information
Patent Citations
A high-temperature resistant heat-insulating coating, its preparation method and application
CN103725074B
A reflective heat-insulating multi-colored coating and its preparation method and application
CN116851235B
Flame-retardant thermal-insulation multilayer film
CN105346175A
Composite titanium yellow pigment and preparation method thereof
CN118852893A
Modified silica-coated pigment, its production and composition containing the same
JP2001011342A